PKM Pengenalan Augmented 3D Reality Menggunakan Unity pada Universitas Teknologi Mataram - Ahmad Chusyairi; Didik Setiyadi; Saludin Saludin; Rully Pramudita; Ismail Marzuki; Samhana Suryati Subari (IKIP PGRI Bojonegoro, 2021)
ABSTRACTMataram Technology University (UTM Mataram) manages the Faculty of Information and Communication Technology (FTIK) which houses 5 (five) study programs: Informatics Engineering, Computer Systems Engineering, Information Technology, Information Systems, and Software Engineering. The background in this PkM is the lack of understanding of 1st-semester students who take the course Introduction to Information Technology regarding Augmented 3D Reality (AR). The goal is to increase students' knowledge and skills about AR supported by Unity tools. The PkM method by providing training and demonstrations online in the form of Zoom media, Live YouTube, and Google Drive Links, 5 modules contains module 1 about introduction to AR and Unity, module 2 about downloading Unity, module 3 about Unity installation, module 4 about basic tutorials and module 5 about project installation on android. The evaluation was given in the form of a PkM questionnaire which 144 participants were filled in. The result is an increase in the participants' understanding, knowledge, and skills about AR with the Unity tool in the FTIK UTM Mataram and on the Good and Very Good assessment of 82.92%. Keywords: Augmented 3D Reality, Unity, UTM Mataram ABSTRAKUniversitas Teknologi Mataram (UTM Mataram) mengelola Fakultas Teknologi Informasi dan Komunikasi (FTIK) yang menaungi 5 (lima) prodi: Teknik Informatika, Rekayasa Sistem Komputer, Teknologi Informasi, Sistem Informasi dan Rekayasa Perangkat Lunak. Latar belakang dalam PkM ini adalah kurangnya pemahaman mahasiswa semester 1 yang mengambil matakuliah Pengantar Teknologi Informasi mengenai Augmented 3D Reality (AR). Tujuannya adalah meningkatkan pengetahuan dan keterampilan mahasiswa mengenai AR yang didukung tool Unity. Metode PkM dengan memberikan pelatihan dan demonstrasi melalui daring yang berupa media Zoom, Live YouTube dan Link Google Drive modul yang 5 berisi: modul 1 tentang pengenalan AR dan Unity, modul 2 tentang download Unity, modul 3 tentang instalasi Unity, modul 4 tentang basic tutorial dan modul 5 tentang instalasi project pada android. Evalusi diberikan dalam bentuk angket PkM yang mana diisi 144 peserta. Hasilnya adalah meningkatnya pemahaman, pengetahuan dan keterampilan peserta tentang AR dengan tool Unity pada FTIK UTM Mataram dan pada penilaian Baik dan Baik Sekali sebesar 82,92%. Kata Kunci: Augmented 3D Reality, Unity, UTM Mataram.